درجة مساهمة مواد الإيقاظ في تنمية الذكاء الانفعالي لدى تلاميذ المرحلة الابتدائية - دوسن غالية; مطبوع منى; اشراف: كتفي عزوز (جامعة محمد بوضياف -المسيلة, 2025)
هدفت هذه الدراسة إلى الكشف عن دور مواد الإيقاظ (الرسم، الموسيقى، والتربية البدنية) في تنمية الذكاء الانفعالي لدى تلاميذ المرحلة الابتدائية، وذلك من خلال آراء الأساتذة الذين يُدرّسون هذه المرحلة، لتحقيق هذا الهدف، تم استخدام استبيان موجّه إلى عينة مكوّنة من 50 أستاذًا، وقد كشفت النتائج أن مواد الإيقاظ تساهم بدرجة كبيرة في تعزيز مختلف أبعاد الذكاء الانفعالي عند التلاميذ. حيث أكد الأساتذة أن أنشطة الرسم، التربية الموسيقية، والتربية البدنية تُسهم في تطوير قدرات التلاميذ على التعبير عن مشاعرهم، ضبط انفعالاتهم، وفهم ذواتهم ومحيطهم الاجتماعي، توصي الدراسة بضرورة إيلاء هذه المواد مكانة أكبر ضمن المناهج التربوية، وتوفير تكوين متخصص للأساتذة لتفعيل دورها في تنمية الذكاء الانفعالي لدى المتعلمين.  الكلمات المفتاحية: مواد الإيقاظ ؛ الذكاء الإنفعالي ؛ الرسم، الموسيقى، التربية بدنية. Summary: This study aimed to explore the role of mindfulness materials (drawing, music, and physical education) in developing emotional intelligence among primary school students. This was achieved through the opinions of teachers who teach at this level. To achieve this goal, a questionnaire was administered to a sample of 50 teachers. The results revealed that mindfulness materials significantly contribute to enhancing various dimensions of emotional intelligence among students. The teachers confirmed that drawing, music education, and physical education activities contribute to developing students' abilities to express their feelings, regulate their emotions, and understand themselves and their social environment. The study recommends that these materials be given greater prominence within educational curricula and that specialized training be provided for teachers to enhance their role in developing learners' emotional intelligence.  key words: mindfulness materials; emotional intelligence; drawing, music, physical education.